Steel for offshore platform mooring chain with tensile strength of 1200 MPa and manufacturing method thereof

By rationally designing chemical components and process flow in the steel for mooring chains of marine platforms and forming a composite matrix structure, the problems of insufficient tensile strength and low-temperature impact toughness of steel in the prior art are solved, and the comprehensive performance improvement of high strength, toughness and plasticity are achieved.

CN119571189AInactive Publication Date: 2025-03-07BAOSHAN IRON & STEEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311151840.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While existing marine platform mooring chain steel is difficult to meet high tensile strength and good low-temperature impact toughness in deep-sea environments, it also has problems of low elongation and insufficient cross-sectional shrinkage.

Method used

By rationally designing chemical components, including elements such as C, Si, Mn, Cr, Mo, Ni, Cu, Nb, V, Ti, Ca and Al, the ratio of Cr/V is controlled between 6.0 and 20.0, and a controlled rolling and cooling process, quenching and tempering process are used to form tempered martensite and tempered bainite complex phase matrix structures.

Benefits of technology

The steel is achieved with ultra-high tensile strength (≥1200MPa), high yield strength (≥1000MPa), good low-temperature impact toughness (-20℃ Xia's impact work Akv ≥65J), high elongation (≥12%) and cross-section shrinkage (≥50%), which significantly improves the strength, toughness and plasticity of the steel for mooring chains.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571189A_ABST
    Figure CN119571189A_ABST
Patent Text Reader

Abstract

The invention discloses steel for a mooring chain and a manufacturing method of the steel. The steel for the mooring chain comprises the following chemical elements in percentage by mass: 0.250 to 0.350 percent of C, 0.10 to 0.50 percent of Si, 1.20 to 1.50 percent of Mn, 1.20 to 2.00 percent of Cr, 0.45 to 0.75 percent of Mo, 2.50 to 3.50 percent of Ni, less than or equal to 0.20 percent of Cu, 0.02 to 0.10 percent of Nb, 0.10 to 0.25 percent of V, 0.001 to 0.003 percent of Ti, less than or equal to 0.005 percent of Ca and 0.01 to 0.05 percent of Al, and the components of the steel for the mooring chain meet the condition that Cr / V is more than or equal to 6 and less than or equal to 20. The steel has good strength, low-temperature toughness and plasticity, and can be used for manufacturing R7-grade high-performance ocean platform mooring chains and used as steel for ultrahigh-toughness structures and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of steel for offshore platform mooring chains, and in particular to steel for offshore platform mooring chains with a tensile strength of 1200 MPa and a manufacturing method thereof. Background Art

[0002] With the development of deep-sea marine resources, the size of offshore platforms, the complexity of structures and functions, and the requirements for offshore platform mooring chains are also increasing. The use environment of offshore platform mooring chains is harsh, and they need to withstand high tensile loads, seawater impact during wave movement, seawater erosion and microbial corrosion. The steel used for offshore platform mooring chains currently mainly includes R3, R3S, R4, R4S, R5, R6, etc., and the corresponding tensile strengths are 690MPa, 770MPa, 860MPa, 960MPa, 1000MPa and 1100MPa respectively. In deep-sea areas with a depth of more than 1000m, the fixation of offshore platforms requires very high loads. If lower-grade mooring chain products are used, the chain diameter needs to be expanded, and the expansion of the chain diameter will make the chain too heavy, and even cause the chain to break due to excessive deadweight load. Therefore, large offshore platforms require mooring chain steel with higher strength levels and higher impact toughness to achieve weight reduction of mooring chains under high loads.

[0003] There are many studies on high-strength and tough steels at home and abroad. Usually, high-strength and tough steels that meet the mechanical properties requirements are produced by selecting appropriate chemical compositions and using quenching and tempering treatment. High-strength steels are produced by controlled rolling and controlled cooling. It is difficult to control during the rolling and cooling process, which affects the overall uniformity of the mechanical properties of the steel. High-strength steels are produced by quenching and tempering processes. By optimizing the content of alloy elements and carbon elements, the hardenability of the steel is improved, and the steel forms a martensitic structure during the cooling process. Martensite has a square lattice structure, in which carbon is dissolved in the body-centered cubic lattice of iron atoms, so that the bcc lattice is extended along the c-axis direction. This type of structure has high strength and hardness. However, high-strength steels mainly based on martensite have poor low-temperature impact energy due to their high dislocation density. There are high-density dislocations and subgrain boundaries inside martensitic high-strength steels. When tiny defects such as microcracks occur during the tensile process, they will quickly break and fail, resulting in lower elongation. Considering the requirements of offshore platforms for mooring chains and the current research and development progress of high-strength and toughness products, it is necessary to develop steel with better strength-toughness matching and excellent elongation properties. Summary of the invention

[0004] In view of the above technical problems, the first aspect of the present invention provides a steel for a mooring chain, which, in addition to containing more than 90% of Fe and unavoidable impurities, further contains the following chemical elements in terms of mass percentage:

[0005] C: 0.250-0.350%, Si: 0.10-0.50%, Mn: 1.20-1.50%, Cr: 1.20-2.00%, Mo: 0.45-0.75%, Ni: 2.50-3.50%, Cu≤0.20%, Nb: 0.02-0.10%, V: 0.10-0.25%, Ti: 0.001-0.003%, Ca≤0.005%, Al: 0.01-0.05%, and the composition of the steel for mooring chains satisfies 6.0≤Cr / V≤20.0. The mass percentages of the corresponding elements shall be entered in the calculation.

[0006] In the present invention, the mass ratio of Cr and V in the steel needs to be controlled between 6.0 and 20.0. If the Cr / V value is lower than 6.0, the carbide content of Cr is low, the number of precipitated carbides is reduced, and it is also unfavorable for low-temperature impact; if the Cr / V value is higher than 20.0, Cr is easy to form M23C6 type coarse carbides in the steel, which deteriorates the impact energy. Preferably, 8.0≤Cr / V≤12.0.

[0007] Preferably, the above-mentioned steel for mooring chain contains the following chemical elements in mass percentage:

[0008] C: 0.250-0.350%, Si: 0.10-0.50%, Mn: 1.20-1.50%, Cr: 1.40-2.00%, Mo: 0.45-0.75%, Ni: 2.50-3.50%, Cu≤0.20%, Nb: 0.02-0.10%, V: 0.10-0.25%, Ti: 0.001-0.003%, Ca≤0.005%, Al: 0.01-0.05%, the balance is Fe and unavoidable impurities; and the composition of the steel for mooring chains satisfies 6≤Cr / V≤20, and the mass percentages of the corresponding elements are entered in the calculation.

[0009] Preferably, the impurity elements satisfy the following conditions in terms of mass percentage: P≤0.015%, S≤0.003%, H≤0.0002%.

[0010] Preferably, the microstructure of the steel for mooring chain contains tempered martensite and tempered bainite; more preferably, the microstructure of the steel for mooring chain consists of tempered martensite and tempered bainite; more preferably, the steel for mooring chain contains more than 90 volume % of tempered martensite and less than 10 volume % of tempered bainite; most preferably, the steel for mooring chain consists of more than 90 volume % of tempered martensite and less than 10 volume % of tempered bainite.

[0011] Preferably, the yield strength of the steel for the mooring chain is ≥1000 MPa, the tensile strength Rm is ≥1200 MPa, the Charpy impact energy Akv at -20°C is ≥65 J, the elongation A is ≥12%, and the cross-sectional shrinkage is ≥50%.

[0012] Preferably, the strength-plasticity-toughness product Rm*A*Akv of the steel for mooring chains is above 1500 GPa%J, preferably above 1700 GPa%J.

[0013] A second aspect of the present invention provides a method for manufacturing the above-mentioned steel for mooring chain, comprising the following steps performed in sequence:

[0014] 1) Smelting and casting molten steel to obtain ingots;

[0015] 2) heating and forging or rolling the ingot to obtain a rolled steel billet;

[0016] 3) quenching the rolled steel billet; and

[0017] 4) Tempering.

[0018] Preferably, in step 2), the ingot is heated to a temperature of 1050-1250° C. Within this temperature range, carbonitrides of Nb and V and carbides of Cr and Mo are partially or completely dissolved in austenite. In the subsequent rolling / forging and cooling process, Nb and V form fine carbonitrides, which pin austenite grain boundaries and refine the rolled structure of the steel; Cr and Mo dissolved in austenite improve the hardenability of the steel and improve the hardenability of martensite during quenching.

[0019] Preferably, in step 2), the ingot is heated and rolled once, and the ingot is directly rolled to the size of the final product, wherein the heating temperature is 1050-1250°C, and the final rolling or final forging temperature is 850-1020°C.

[0020] In one embodiment, the ingot is first heated and rolled for the first time, and the ingot is rolled to a specified intermediate billet size, and then the intermediate billet is heated and rolled for the second time, and the intermediate billet is rolled to the size of the final product, wherein the first heating temperature is 1050-1250°C, and the first final rolling or final forging temperature is 850-1020°C; the second heating temperature is 1070-1150°C, and the second final rolling or final forging temperature is 870-980°C.

[0021] The present invention sets the final rolling or final forging temperature within the above range, which is beneficial to the formation of a refined bainite and martensite multiphase matrix structure in the steel and the precipitation of fine carbonitrides, thereby improving the mechanical properties of the steel.

[0022] Preferably, in step 2), air cooling or slow cooling is performed after rolling and before quenching; preferably, the cooling rate of the air cooling or slow cooling is 20° C. / hour or less.

[0023] Preferably, during quenching, the rolled steel billet is heated to an austenitizing temperature of 840-1020°C for 50-250 minutes, followed by water quenching. By heating the steel billet to this temperature range, the carbonitrides of Nb, V, Ti, Cr and Mo are dissolved in whole or in part, thereby avoiding excessive coarsening of austenite grains, achieving the purpose of grain refinement after quenching, and improving the strength and toughness of the steel; during the quenching cooling process, the alloy elements dissolved in the austenite improve the hardenability of the steel, making the final martensite finer, and such a structure has ultra-high strength and good toughness.

[0024] Preferably, the tempering temperature is 570-630°C, and the tempering time is 90-300 minutes. During the quenching process, the steel forms lower bainite and martensite structures with a large defect density, a large strain storage energy inside, and an uneven internal stress distribution. During the high-temperature tempering process, Nb and V will form fine carbides with C and N. At the same time, Cr and Mo will also form fine carbides and precipitate during the high-temperature tempering process, which improves the strength and toughness matching of the steel; at the same time, due to the annihilation of high-density dislocations and the movement of small-angle grain boundaries, the microstructure of the steel is more uniform, which improves the phenomenon of low elongation after low-temperature tempering. Within the tempering temperature range described in the present invention, it can be ensured that the steel has good toughness and plasticity; optionally, air cooling or water cooling is performed after tempering.

[0025] The present invention develops a low-temperature ultra-high strength and high-toughness steel by rationally designing the chemical composition. This steel is an ultra-high strength steel with a tensile strength of 1200MPa. Further combined with the optimized process, especially the tempering process is adopted for the rolled or forged bars after quenching, to form a tempered martensite and tempered bainite matrix structure, and refined carbides are precipitated on the matrix, which eliminates the internal stress of the steel and has good structural uniformity.

[0026] The steel material of the present invention has reasonable composition and process design, a wide process window, and can be commercially produced in batches on a bar or plate production line.

[0027] The steel produced by the present invention has a yield strength greater than or equal to 1000MPa, a tensile strength greater than or equal to 1200MPa, a Charpy impact energy Akv (-20°C) greater than or equal to 65J, an elongation greater than or equal to 12%, a cross-sectional shrinkage greater than or equal to 50%, and a strength-plasticity-toughness product: Rm*A*AKv greater than or equal to 1500GPa%J. This type of ultra-high strength steel has good strength, low-temperature toughness and plasticity, and can be used to produce bars for R7 offshore platform mooring chains. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a metallographic photograph of the steel for mooring chains according to Example 3 of the present invention. DETAILED DESCRIPTION

[0029] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0030] In this article, the yield strength, tensile strength Rm, elongation A and cross-sectional reduction Z are measured with reference to GB / T 228.1-2010 “Tensile test of metallic materials Part 1: Room temperature test method”.

[0031] The Charpy impact energy Akv (-20℃, longitudinal) is determined in accordance with GB / T 229-2020 "Charpy Pendulum Impact Test Method for Metallic Materials".

[0032] The chemical composition of the steel for mooring chains of the present invention is quite different from that of the steel in the prior art.

[0033] For example, Chinese patent application CN103667953A (published on March 26, 2014) discloses a low environmental crack sensitivity ultra-high strength and toughness mooring chain steel and a manufacturing method thereof, wherein the steel composition is, by mass percentage, C 0.12-0.24, Mn 0.10-0.55, Si 0.15-0.35, Cr 0.60-3.50, Mo 0.35-0.75, N≤0.006, Ni 0.40-4.50, Cu≤0.50, S≤0.005, P 0.005-0.025, O≤0.0015, H≤0.00015, and the remainder is Fe and unavoidable impurities. The tensile strength (Rm) of the steel is ≥1110MPa, the yield strength ratio (YR) is 0.88-0.92, the elongation (A) is ≥12%, the cross-sectional shrinkage (Z) is ≥50%, and the impact energy (Akv) at -20°C is ≥50J. The components of the high-performance marine mooring chain steel also include one or more of the microalloying elements V, Al, Nb, Ti, Ca, and RE, and the content thereof is V 0.05-0.25, Al 0.01-0.06, Nb 0.005-0.05, Ti0.002-0.10, Ca0.005-0.004, RE0.010-0.025, Sn+Sb+As≤0.035, all in mass percentage. The patent adopts the above components and two quenching processes to obtain high-strength and tough mooring chain steel.

[0034] On the one hand, the composition difference between the mooring chain steel of the present invention and CN103667953A lies in the different contents of C, Mn, Mo, Ti and rare earth element RE. Specifically, the present invention utilizes the design of C element, Ni element, Mo element and rare earth element RE, combined with the optimization of elements such as Mn and Cr, to form a tempered bainite and tempered martensite multiphase microstructure, which is different from the microstructure (upper bainite + lower bainite + martensite, upper bainite + lower bainite or upper bainite) formed in CN103667953A.

[0035] On the other hand, the organizational design ideas for achieving high strength and toughness in the technical solutions of the present invention and CN103667953A are completely different, so the component system and process system used to form such organizations are completely different. The difference between the patent of the present invention and the preparation method in CN103667953A is that the quenching treatment mentioned in CN103667953A is two quenching treatments, and the steel of the present invention can achieve high strength and toughness matching by a single quenching process, saving the quenching process, reducing production costs and carbon emissions, and is an environmentally friendly steel. In addition, the tensile strength of the steel in the present invention reaches more than 1200MPa, and the tensile strength of the steel disclosed in CN103667953A exceeds 1110MPa. The mechanical properties of the steel for mooring chains of the present invention are significantly better.

[0036] Chinese patent application CN112011727A (publication date December 1, 2020) discloses an ultra-high strength and low-temperature toughness steel, an ultra-high strength and low-temperature toughness rod and a manufacturing method thereof. The chemical elements of the steel are calculated in mass percentage as follows: C: 0.150~0.250%, Si: 0.10~0.50%, Mn: 0.60~1.50%, Cr: 0.30~1.20%, Mo: 0.20~0.80%, Ni: 2.00~4.00%, Nb: 0~0.10%, B: 0.0010~0.0050%, V: 0~0.12%, Ti: 0.003~0.06%, Al: 0.01~0.08%, and the balance is Fe and unavoidable impurities. The mechanical properties of the steel are as follows: yield strength ≥950MPa, tensile strength ≥1150MPa, Charpy impact energy Akv ≥75J below -20°C, elongation ≥15%, and section shrinkage ≥55%.

[0037] The difference between the steel of the present invention and that of CN112011727A is that the contents of C, Mo and Ti are completely different. The present invention does not contain B, and at the same time optimizes the composition range of alloy elements such as Mn, Mo, Nb, V, and limits the content of H element. The use of the alloy element range defined by the present invention can make the steel form tempered martensite and tempered bainite microstructures, showing ultra-high toughness mechanical properties. In addition, the tensile strength of the steel for mooring chains of the present invention is greater than or equal to 1200MPa, and the yield strength is greater than or equal to 1000MPa. The tensile strength of the steel of CN112011727A is greater than or equal to 1150MPa. The strength grade of the steel for mooring chains of the present invention is significantly higher than that of CN112011727A. The technical scheme of the present invention is completely different from the technical route of CN112011727A in terms of steel organization design, composition and process design.

[0038] In the steel for offshore platform mooring chain of the present invention, the design principles of each chemical element are specifically described as follows:

[0039] C: C added to steel can improve the hardenability of the steel, so that the steel forms a low-temperature phase transformation structure with higher hardness during the quenching and cooling process to improve the strength of the steel. The increase in C content will increase the proportion of hard phases such as martensite and lower bainite in the steel, and will also increase the number of carbide precipitation phases in the matrix, forming a dispersion strengthening effect to improve the hardness of the steel. If the C content is too low, it will lead to low content of low-temperature phase transformation structures such as martensite and lower bainite, and it will not be possible to obtain a higher tensile strength. However, the C content cannot be too high, otherwise it will lead to a decrease in toughness. Therefore, in the present invention, the C content is set to 0.250-0.350wt.%.

[0040] Si: Si replaces Fe atoms in steel by substitution, forming a solid solution strengthening effect, hindering dislocation movement, and effectively improving the strength of steel. Si is an element that inhibits the formation of ferrite and can reduce the diffusion ability of C in ferrite. Therefore, during tempering, an appropriate amount of Si can avoid the formation of coarse carbides that precipitate at defects. However, too high a Si content will reduce the low-temperature impact toughness of the steel. Therefore, in the present invention, the Si content is set to: 0.10~0.50wt.%.

[0041] Mn: During the quenching process of steel, Mn will inhibit diffusion-type phase transformation, improve the hardenability of steel, and form low-temperature phase transformation structure. This type of structure has higher strength, and Mn has a certain deoxidation effect. However, too high Mn content will lead to the formation of more residual austenite, reduce the yield strength of steel, and manganese-containing steel has greater overheat sensitivity. In addition, too high Mn content will cause the austenite grains to grow easily during quenching heating, and Mn will promote the segregation of harmful elements at the grain boundaries, increasing the temper brittleness tendency of steel. Therefore, the Mn content is set to 1.20-1.50wt.% in the present invention. Mn within this range is conducive to improving the strength and hardenability of steel, while avoiding the formation of too much residual austenite.

[0042] P: P in steel segregates at grain boundaries, which reduces the binding energy of the grain boundaries, deteriorates the low-temperature impact performance of the steel, and aggravates the cold brittleness of the steel. P segregated at grain boundaries causes the steel to fracture along the grain when subjected to impact loads, forming larger cleavage planes, and reducing the energy absorbed by the steel when subjected to impact. In the present invention, the P content is controlled to be no more than 0.015wt.%, so as to ensure the low-temperature impact toughness of the ultra-high strength steel.

[0043] S: The solubility of S in delta ferrite and austenite is very low. During the solidification of molten steel, S will be segregated to form more sulfide inclusions, which will harm the ultrasonic flaw detection performance and low-temperature impact performance of steel. In addition, S will form low-melting point FeS with Fe, showing hot brittleness. The present invention controls the S content to avoid the damage of coarse sulfides to the impact performance. Therefore, the S content is set to no more than 0.003wt.% in the present invention to ensure that the steel has good low-temperature impact performance.

[0044] Cr: Adding Cr to steel will reduce the driving force of γ-α phase transformation, inhibit the diffusion phase transformation of steel, improve the hardenability of steel, form a hardened martensitic structure, and obtain steel with higher strength. At the same time, if the carbide of Cr is not completely dissolved during the heating process, it will inhibit the growth of austenite grains. If the Cr content is too high, coarse carbides will be formed, which will deteriorate the low-temperature impact performance. Therefore, the Cr content is set to 1.20-2.00wt.%, preferably 1.40-2.00wt.%, in the present invention to ensure the strength and low-temperature impact performance of the steel.

[0045] Mo: Mo can delay the transformation of proeutectoid ferrite, promote the formation of acicular ferrite and bainite, and improve the strength and toughness of low alloy steel. Mo can also increase the solid solubility of microalloying elements (Nb, V, Ti) in austenite, delay the precipitation of microalloy carbonitrides, and allow more microalloying elements to be retained until precipitation during tempering, thereby producing a greater precipitation strengthening effect. In addition, Mo can be dissolved in the lattice of microalloy carbonitrides precipitated in ferrite to form (M, Mo) (C, N) (M is a microalloying element), which can not only increase the volume fraction of the precipitated phase, but also significantly refine the size of the microalloy precipitates, thereby enhancing the precipitation strengthening effect. Mo-containing microalloy carbonitrides have good thermal stability and are not easy to coarsen at high temperatures. However, Mo is a precious alloying element, and adding higher Mo will lead to increased costs. Therefore, the Mo content is set to 0.45-0.75wt.% in the present invention to obtain a high-strength and toughness match.

[0046] Nb: Nb is added to steel to inhibit the recrystallization of steel. Nb exists in steel as a replacement solute atom. Nb atoms are larger than Fe atoms and tend to be concentrated at dislocation lines, which have a strong dragging effect on dislocation movement. At the same time, Nb can form interstitial intermediate phases such as NbC and NbN in steel. During the recrystallization process, it hinders the pinning of dislocations and the migration of subgrain boundaries, effectively refines the grains, and prevents the coarsening of the grains at the weld during welding, which causes a decrease in impact performance. However, the Nb content is relatively high, and coarse NbC particles will be formed under high-temperature tempering conditions, which will deteriorate the low-temperature impact energy of the steel. Therefore, in order to cooperate with other alloying elements to ensure that the steel has good mechanical properties, the Nb content is set to 0.02-0.10wt.% in the present invention.

[0047] Ni: Ni exists in the steel in the form of solid solution. In the component system of the present invention, Ni exists in the FCC phase of Fe-Ni-Mn, which can reduce the stacking fault energy and reduce the resistance to dislocation movement. In addition, the distribution of Ni on the θ / α interface reduces the carbon flux to 0, thereby hindering the growth of cementite, effectively preventing the abnormal growth of carbides, improving the toughness of the steel matrix, and improving the low-temperature impact performance of steel. On the other hand, Ni is an austenite forming element, and too high a Ni content will lead to an excessively high content of residual austenite in the steel, reducing the strength of the steel. Therefore, the Ni content is set at 2.50-3.50wt.% in the present invention to ensure the low-temperature impact toughness and strength of the steel.

[0048] Cu: When Cu is added to steel, fine nano-scale ε-Cu will be precipitated during the tempering process, which will improve the strength of the steel. At the same time, adding a certain amount of Cu is beneficial to improving the corrosion resistance of the steel. However, due to the low melting point of Cu, if the Cu content is too high, copper will be enriched at the grain boundary during the heating austenitization process, resulting in weakening of the grain boundary and cracking. Therefore, the Cu content is set to no more than 0.20wt.% in the present invention.

[0049] V: In steel, V and C form VC. Small VC will hinder dislocation to a certain extent. At the same time, VC has a high dissolution temperature, which can effectively prevent grain boundary movement, refine grains, and improve the strength of steel. However, under the condition of high temperature tempering, if the C and V contents are both high, coarse VC particles will be formed, reducing the impact resistance of steel. Therefore, the V content is set to 0.10-0.25wt.% in the present invention to ensure the mechanical properties of steel.

[0050] Al: Al forms fine AlN precipitation during steelmaking, which inhibits the growth of austenite grains during the subsequent cooling process, thereby refining the austenite grains and improving the toughness of steel at low temperatures. In addition, Al is a good deoxidizer and can effectively reduce the oxygen content in steel. However, too high an Al content will lead to the formation of larger Al oxides, making the steel unsuitable for ultrasonic flaw detection, and coarse aluminum oxide hard inclusions will deteriorate the fatigue properties of the steel. Therefore, the Al content is set to 0.01-0.05wt.% in the present invention to improve the toughness of the steel.

[0051] Ti: Ti exists in the steel in the form of solid solution. The carbonitride formed by it can pin the austenite grain boundary, prevent the austenite grains from being too coarse, achieve the purpose of grain refinement after quenching, and improve the strength and toughness of the steel. However, if the Ti content is too high, coarse TiN will be precipitated, resulting in reduced impact and fatigue properties of the steel. And during the tempering process, if the Ti content is too high, the fluctuation amplitude of the low-temperature impact energy will increase. Therefore, the Ti content in the present invention is controlled at 0.001-0.003wt.%.

[0052] Ca: A proper amount of Ca element is added to steel to form CaS, which can improve the size and morphology of inclusions and improve the low-temperature impact toughness of steel. However, too high Ca content will cause the size of inclusions in the steel to exceed the standard and may cause nozzle blockage, affecting the castability of molten steel. Therefore, the Ca content in the present invention is controlled below 0.005wt.%.

[0053] H: H is affected by the hydrostatic pressure field of edge dislocations in the steel and will gather at defects to form hydrogen embrittlement. The density of dislocations and subgrain boundaries in steels with a tensile strength level of 1100MPa and above is high. If the H content is too high, more H atoms will be enriched at the defects after the steel is quenched and tempered. The H atoms will gather to form H molecules, causing delayed fracture of the steel. If rods with a high H content are used to produce offshore platform mooring chains, the corrosion of the mooring chains by seawater and the penetration of H will cause delayed cracking of high-strength mooring chains during use, endangering the safety of the offshore platform. Therefore, the H content in the steel of the present invention does not exceed 0.0002wt.%.

[0054] Unless otherwise specified, the element contents in the present invention refer to mass percentages, and the steel structure contents in the present invention refer to volume fractions.

[0055] The technical solution of the present invention is further described in detail below in conjunction with the examples. It should be clear that the following examples are only used to describe the specific implementation methods of the present invention and are not intended to limit the protection scope of the present invention in any way.

[0056] Examples 1-6 and Comparative Examples 1-7

[0057] The mooring chain steels of Examples 1-6 and Comparative Examples 1-7 of the present invention are prepared by the following steps:

[0058] 1) Smelting: The molten steel is smelted in an electric furnace or a converter according to the formula shown in Table 1.

[0059] 2) Casting: The molten steel obtained from smelting is cast into billets or ingots by mold casting or continuous casting.

[0060] 3) Heating and forging or rolling: The cast billet or ingot is heated and forged or rolled to obtain a rolled billet.

[0061] The ingots in Examples 3, 5-6 and Comparative Examples 1, 4, 6-7 are heated and rolled only once, and the ingots are directly rolled into the final size of the finished product, wherein the heating temperature of the ingots in Examples 3, 5-6 is 1050-1250°C, and the final rolling or final forging temperature is 850-1020°C; the ingots in Examples 1-2, 4 and Comparative Examples 2-3, 5 are heated and rolled for the first time, and the ingots are rolled to the specified intermediate billet size, and then the intermediate billet is heated and rolled for the second time, and the intermediate billet is rolled to the size of the final product, wherein the first heating temperature of the ingots in Examples 1-2, 4 is 1050-1250°C, and the first final rolling or final forging temperature is 850-1020°C; the second heating temperature is 1070-1150°C, and the second final rolling or final forging temperature is 870-980°C; the diameter of the finished steel is between 20-200mm, which is adjusted according to actual needs.

[0062] 4) The rolled steel billet is slowly cooled at a cooling rate of 20°C / h or less.

[0063] 5) Quenching: During quenching, the rolled steel billet is heated to an austenitizing temperature of 840 to 1020°C for 60 to 240 minutes, and water quenching is performed after austenitizing.

[0064] 6) Tempering: The tempering temperature is 570-630°C, and the tempering time is 90-300 minutes.

[0065] 7) Water cooling.

[0066] The elemental compositions of the steels of Comparative Examples 1-3 are not within the scope defined by the present invention, and certain manufacturing process parameters of the steels of Comparative Examples 4-7 do not meet the requirements of the present invention.

[0067] The specific process parameters of Examples 1-6 and Comparative Examples 1-7 are shown in Table 2 below.

[0068] The steels of Examples 1-6 and Comparative Examples 1-7 finally obtained were sampled respectively, and the microstructure and mechanical properties of each steel sample were tested. The test results are recorded in Table 3.

[0069] Figure 1 It is the electron microscope photo of Example 3, Figure 1 It can be seen that the microstructure of the steel of Example 3 is a duplex structure of tempered martensite and tempered bainite;

[0070] In Table 3, the longitudinal impact energy Akv at -20℃ records the values ​​of three parallel tests. The average value of the three parallel test results is used when calculating the product of strength-plasticity-toughness Rm*A*Akv.

[0071] It can be seen from Table 3 that the yield strength of the steel of Examples 1-6 of the present invention is greater than or equal to 1000 MPa, the tensile strength is greater than or equal to 1200 MPa, the Charpy impact energy Akv (-20°C) is greater than or equal to 65 J, the elongation is greater than or equal to 12%, the cross-sectional shrinkage is greater than or equal to 50%, and the product of strength-plasticity-toughness: Rm*A*Akv is greater than or equal to 1500 GPa% J. The mooring chain steel of the present invention has good strength, low temperature toughness and plasticity, and can be used to manufacture R7-level high-performance offshore platform mooring chains and ultra-high strength and toughness structural steel.

[0072] Since the element composition of the steel or the specific conditions of the manufacturing process of Comparative Examples 1-7 do not meet the requirements of the present invention, at least one of the mechanical properties of the obtained steel cannot meet the requirements of the present invention.

[0073] Table 1 (Unit: wt.%, the remainder is Fe and impurities other than P, S, and H)

[0074] C Si Mn P S Cr Mo Nb Ni Cu V Al Ti Ca H Cr / V Example 1 0.255 0.50 1.50 0.015 0.002 2.0 0.75 0.06 2.50 0.20 0.25 0.05 0.001 0.005 0.00015 8.00 Example 2 0.273 0.43 1.43 0.011 0.002 1.93 0.65 0.08 2.70 0.14 0.19 0.04 0.002 0.001 0.00020 10.16 Example 3 0.303 0.34 1.35 0.009 0.001 1.75 0.64 0.05 2.93 0.17 0.17 0.03 0.002 0.002 0.00012 10.29 Example 4 0.314 0.23 1.32 0.007 0.003 1.86 0.53 0.03 3.00 0.10 0.15 0.04 0.0015 0.003 0.00010 12.40 Example 5 0.331 0.22 1.26 0.010 0.002 1.58 0.59 0.02 3.30 0.06 0.14 0.02 0.003 0.003 0.00012 11.29 Example 6 0.350 0.10 1.25 0.008 0.001 1.40 0.45 0.10 3.50 0 0.2 0.01 0.001 0 0.00007 7.00 Comparative Example 1 0.205 0.21 1.32 0.006 0.002 1.83 0.52 0.06 3.15 0.09 0.16 0.028 0.003 0.0013 0.00014 11.44 Comparative Example 2 0.289 0.23 1.28 0.010 0.001 1.90 0.56 0.03 3.03 0.03 0.05 0.031 0.002 0.0015 0.00011 38.00 Comparative Example 3 0.293 0.24 1.29 0.007 0.001 0.5 0.61 0.04 3.10 0.05 0.13 0.032 0.0024 0.0016 0.00015 3.85 Comparative Example 4 0.282 0.42 1.36 0.011 0.002 1.93 0.65 0.08 2.70 0.14 0.25 0.04 0.002 0.001 0.00020 7.72 Comparative Example 5 0.304 0.33 1.38 0.009 0.001 1.85 0.64 0.05 2.93 0.17 0.17 0.03 0.002 0.002 0.00012 10.88 Comparative Example 6 0.313 0.23 1.31 0.007 0.003 1.76 0.53 0.03 3.00 0.10 0.15 0.04 0.0015 0.003 0.00010 11.73 Comparative Example 7 0.313 0.23 1.31 0.007 0.003 1.76 0.53 0.03 3.00 0.10 0.15 0.04 0.0015 0.003 0.00010 11.73

[0075] Table 2

[0076]

[0077] Table 3

[0078]

[0079] All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.

[0080] Although the present invention has been described by reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.

Claims

1. A steel for a mooring chain, characterized in that: The mooring chain steel contains, in addition to more than 90% of Fe and unavoidable impurities, the following chemical elements in terms of mass percentage: C: 0.250-0.350%, Si: 0.10-0.50%, Mn: 1.20-1.50%, Cr: 1.20-2.00%, Mo: 0.45-0.75%, Ni: 2.50-3.50%, Cu≤0.20%, Nb: 0.02-0.10%, V: 0.10-0.25%, Ti: 0.001-0.003%, Ca≤0.005%, Al: 0.01-0.05%, and the composition of the steel for mooring chains satisfies 6≤Cr / V≤20, and the mass percentages of the corresponding elements are entered in the calculation.

2. The mooring chain steel according to claim 1, characterized in that: The mooring chain steel contains the following chemical elements in mass percentage: C: 0.250-0.350%, Si: 0.10-0.50%, Mn: 1.20-1.50%, Cr: 1.20-2.00%, Mo: 0.45-0.75%, Ni: 2.50-3.50%, Cu≤0.20%, Nb: 0.02-0.10%, V: 0.10-0.25%, Ti: 0.001-0.003%, Ca≤0.005%, Al: 0.01-0.05%, and the balance is Fe and unavoidable impurities; and the composition of the steel for mooring chains satisfies 6≤Cr / V≤20, and the mass percentages of the corresponding elements are entered in the calculation.

3. The mooring chain steel according to claim 1 or 2, characterized in that: The impurity elements satisfy the following in terms of mass percentage: P≤0.015%, S≤0.003%, H≤0.0002%.

4. The steel for mooring chain according to claim 1 or 2, characterized in that: The microstructure of the steel for a mooring chain includes tempered martensite and tempered bainite.

5. The mooring chain steel according to claim 4, characterized in that: The microstructure of the steel for mooring chains is tempered martensite and tempered bainite.

6. The steel for mooring chain according to claim 4, characterized in that: The microstructure of the mooring chain steel includes 90 volume % or more of tempered martensite and 10 volume % or less of tempered bainite.

7. The mooring chain steel according to claim 1 or 2, characterized in that: The yield strength of the mooring chain steel is ≥1000MPa, the tensile strength Rm is ≥1200MPa, the Charpy impact energy Akv at -20°C is ≥65J, the elongation A is ≥12%, and the cross-sectional shrinkage is ≥50%.

8. The mooring chain steel according to claim 7, characterized in that: The product of strength-plasticity-toughness Rm*A*Akv of the mooring chain steel is above 1500 GPa%J.

9. A method for manufacturing the steel for a mooring chain according to any one of claims 1 to 8, characterized in that: The method comprises the following steps performed in sequence: 1) Smelting and casting molten steel to obtain ingots; 2) heating and forging or rolling the ingot to obtain a rolled steel billet; 3) quenching the rolled steel billet; 4) Tempering.

10. The method according to claim 9, characterized in that In step 2), the cast slab is heated to a temperature of 1050-1250°C.

11. The method according to claim 9, characterized in that In step 2), the ingot is heated and rolled once, and the ingot is directly rolled to the size of the final product, wherein the heating temperature is 1050-1250°C, and the final rolling or final forging temperature is 850-1020°C; or, in step 2), the ingot is first heated and rolled for the first time, and the ingot is rolled to the specified intermediate billet size, and then the intermediate billet is heated and rolled for the second time, and the intermediate billet is rolled to the size of the final product, wherein the first heating temperature is 1050-1250°C, and the first final rolling or final forging temperature is 850-1020°C; the second heating temperature is 1070-1150°C, and the second final rolling or final forging temperature is 870-980°C.

12. The method according to claim 9, characterized in that The method also satisfies one or more of the following: The method further comprises air cooling or slow cooling the steel billet after rolling and before quenching; During quenching, the rolled steel billet is heated to an austenitizing temperature of 840-1020°C for 50-250 minutes, followed by water quenching; The tempering temperature is 570-630°C, and the tempering time is 90-300 minutes.

Citation Information

Patent Citations

  • Oceanic mooring chain steel with low environmental crack sensitivity and ultrahigh obdurability and preparation method thereof

    CN103667953A

  • Ultrahigh-strength low-temperature-toughness steel, ultrahigh-strength low-temperature-toughness bar and manufacturing method of ultrahigh-strength low-temperature-toughness bar

    CN112011727A

  • Mid-carbon, nickel, chromium, molybdenum and vanadium alloy steel seamless tube and production method therefore

    CN102861784A

  • Yield ratio control steel with excellent low-temperature impact toughness and manufacturing method thereof

    CN113322420A

  • High-strength steel with excellent weather resistance and manufacturing method thereof

    CN114592153A